D-Antipodal and detour D-Antipodal graphs - V. Venkateswara Rao, P. L. N. Varma, Reddy Babu D., Y. Srinivasa Rao (International Journal of Advanced Science and Technology, 2020)
In this article, we introduce the concept of D-antipodal and detour D-antipodal graphs. We discuss about D-antipodal, self D-antipodal and also detour D-antipodal and self detour D-antipodal graphs of some families of graphs. Also some results are obtained in case of trees.